Repair of Osteochondral Defects With Predifferentiated Mesenchymal Stem Cells of Distinct Phenotypic Character Derived From a Nanotopographic Platform. Issue 7 (June 2020) - Wu, Yingnan; Yang, Zheng; Denslin, Vinitha; Ren, XiaFei; Lee, Chang Sheng; Yap, Fung Ling; Lee, Eng Hin
Background: Articular cartilage has a zonal architecture and biphasic mechanical properties. The recapitulation of surface lubrication properties with high compressibility of the deeper layers of articular cartilage during regeneration is essential in achieving long-term cartilage integrity. Current clinical approaches for cartilage repair, especially with the use of mesenchymal stem cells (MSCs), have yet to restore the hierarchically organized architecture of articular cartilage. Hypothesis: MSCs predifferentiated on surfaces with specific nanotopographic patterns can provide phenotypically stable and defined chondrogenic cells and, when delivered as a bilayered stratified construct at the cartilage defect site, will facilitate the formation of functionally superior cartilage tissue in vivo. Study Design: Controlled laboratory study. Methods: MSCs were subjected to chondrogenic differentiation on specific nanopatterned surfaces. The phenotype of the differentiated cells was assessed by the expression of cartilage markers. The ability of the 2-dimensional nanopattern-generated chondrogenic cells to retain their phenotypic characteristics after removal from the patterned surface was tested by subjecting the enzymatically harvested cells to 3-dimensional fibrin hydrogel culture. The in vivo efficacy in cartilage repair was demonstrated in an osteochondral rabbit defect model. Repair by bilayered construct with specific nanopattern predifferentiated cells was compared with implantation with cell-free fibrin hydrogel, undifferentiated MSCs, and mixed-phenotype nanopattern predifferentiated MSCs. Cartilage repair was evaluated at 12 weeks after implantation. Results: Three weeks of predifferentiation on 2-dimensional nanotopographic patterns was able to generate phenotypically stable chondrogenic cells. Implantation of nanopatterned differentiated MSCs as stratified bilayered hydrogel constructs improved the repair quality of cartilage defects, as indicated by histological scoring, mechanical properties, and polarized microscopy analysis. Conclusion: Our results indicate that with an appropriate period of differentiation, 2-dimensional nanotopographic patterns can be employed to generate phenotypically stable chondrogenic cells, which, when implanted as stratified bilayered hydrogel constructs, were able to form functionally superior cartilage tissue. Clinical Relevance: Our approach provides a relatively straightforward method of obtaining large quantities of zone-specific chondrocytes from MSCs to engineer a stratified cartilage construct that could recapitulate the zonal architecture of hyaline cartilage, and it represents a significant improvement in current MSC-based cartilage regeneration.